Excavation Sequence and Surrounding Rock Mass Stability of Large-Scale Underground Engineering with 8 Tunnels - Zhiqiang Zhang; Mingming He; Fangfang Chen; Ning Li (Advances in Civil Engineering)
In some large-scale hydroelectric power projects, there are more than 3 tunnels that are too close to each other to eliminate the mutual influence during the excavation period, especially for large-scale tunnel groups. In this paper, aimed at analyzing the Bukun hydropower station consisting of 8 tunnels in Malaysia, the displacement, stress, and plastic zone of the surrounding rock mass are analyzed to study the effect of the excavation sequence on the stability of the surrounding rock mass for large-scale tunnel groups. On the one hand, the in situ monitoring of the surface displacement of the rock mass surrounding the tunnel using extensometers is performed to obtain the deformation characteristics on the excavation limit under the typical excavation sequence. On the other hand, a series of elastic-plastic 3D numerical experiments are carried out to explore the displacement characteristics, stability of the large-scale tunnel groups, and safety of the initial supporting system. The results show that the tendencies of the displacement increase corresponding to the tunnel face movement are similar for the three excavation sequences. The displacement under initial excavation sequence 2 (IES2) is the smallest among the three sequences; the area of the plastic zone under IES2 is the smallest among them; and the stresses in the shotcrete layer and axial forces in the rock bolt under the three excavation sequences are within the safety limitation. Initial excavation sequence 2 is an optimized excavation sequence, in which tunnels #1 and #5 are excavated first; after an advance of 3 times the diameter of the tunnel, tunnels #3 and #7 are excavated; tunnels #2 and #6 are excavated after an advance of 3 times diameters; and tunnels #4 and #8 are excavated after an advance of 3 times diameters.